2001
DOI: 10.1029/2000jd000201
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal distribution of enhanced boundary layer BrO concentrations measured by the GOME instrument aboard ERS‐2

Abstract: Abstract. The temporal and spatial distribution of enhanced boundary layer BrO concentrations in both hemispheres during 1997 is presented using observations of the Global Ozone Monitoring Experiment (GOME) on board the European research satellite ERS-2. BrO concentrations (up to 50 ppt) are the major cause for catalytic boundary layer ozone destruction typically observed during polar spring in both hemispheres. While autocatalytic mechanisms are most probably responsible for the release of the observed high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
145
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(157 citation statements)
references
References 35 publications
9
145
0
3
Order By: Relevance
“…14, it stated that, except for the results at high latitudes in spring, the seasonal and latitudinal variations of the tropospheric BrO columns are generally rather small, with a magnitude lying within the uncertainties of the retrieved tropospheric BrO columns. Our analysis tends to confirm the findings of other studies (Fitzenberger et al, 2000;Wagner et al, 2001;Richter et al, 2002;Van Roozendael et al, 2002;Hendrick et al, 2007;Theys et al, 2007) that a tropospheric BrO background with vertical columns of 1-3 × 10 13 molec cm −2 , in addition to the polar BrO emissions occurring in spring, must be present at the global scale for all seasons. This is in contrast to three studies using spectral observations of direct-sun geometry, at Lauder (Schofield et al, 2004), Arrival Heights, Antarctica (Schofield et al, 2006) and in the tropics (Dorf et al, 2008) showing tropospheric columns significantly less i.e.…”
Section: Extra-polar Tropospheric Brosupporting
confidence: 80%
“…14, it stated that, except for the results at high latitudes in spring, the seasonal and latitudinal variations of the tropospheric BrO columns are generally rather small, with a magnitude lying within the uncertainties of the retrieved tropospheric BrO columns. Our analysis tends to confirm the findings of other studies (Fitzenberger et al, 2000;Wagner et al, 2001;Richter et al, 2002;Van Roozendael et al, 2002;Hendrick et al, 2007;Theys et al, 2007) that a tropospheric BrO background with vertical columns of 1-3 × 10 13 molec cm −2 , in addition to the polar BrO emissions occurring in spring, must be present at the global scale for all seasons. This is in contrast to three studies using spectral observations of direct-sun geometry, at Lauder (Schofield et al, 2004), Arrival Heights, Antarctica (Schofield et al, 2006) and in the tropics (Dorf et al, 2008) showing tropospheric columns significantly less i.e.…”
Section: Extra-polar Tropospheric Brosupporting
confidence: 80%
“…The expected lifetime for BrO in this situation is very short (a few minutes based on HO 2 loss mechanism estimate) hence satellite measurements might not be able to observe BrO in an aging plume in contrast to local ground-based measurements. Depending on the exact composition of the plume, rapid recycling on the abundant aerosols could also extend the BrO lifetime in analogy to polar boundary layer events where BrO can be observed over hours and days [Wagner et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…But still, direct measurements of BrO in the mid-latitude troposphere are rare. Hebestreit et al [1999] reported BrO up to 80 parts per trillion (ppt) in the Dead Sea valley and Wagner et al [2001] found BrO at the Caspian Sea using GOME satellite data. Bromide from sea salt deposits is most likely the origin of reactive bromine in this case ('Bromine Explosion' [Platt and Lehrer, 1997;Vogt et al, 1996]).…”
Section: Introductionmentioning
confidence: 99%